Tear Lysozyme in Sjögren´s syndrome, Meibomian gland dysfunction, and non-dry-eye - Berra, Martín (2020)
Purpose: To evaluate the concentration of tear lysozyme in individuals with Sjogren´s syndrome, meibomian gland dysfunction, and non-dry-eye disease. Methods: Ninety subjects were recruited for this study, including 30 with Sjogren´s syndrome, 30 with meibomian gland dysfunction, and 30 with non-dry-eye disease. All subjects were referred to participate in the study based on a “dry eye” investigation. They underwent a complete ocular surface ophthalmic examination encompassing ocular surface disease index, biomicroscopy, tear break-up time, Schirmer test type I, conjunctival vital staining with fluorescein and lissamine green, tear lysozyme concentration, and impression cytology. Results: Clinical tests yielded the following results: ocular surface disease index Sjogren´s syndrome: 64.5 ± 22.6 meibomian gland dysfunction: 43.5 ± 21.4, non-dry-eye disease: 6.7 ± 4.3 (p=0.02 between groups); Schirmer I test (mm/5 min): Sjogren´s syndrome: 4.95 ± 2.25, meibomian gland dysfunction: 13.28 ± 1.53, non-dry-eye disease 13.70 ± 1.39 (p<0.01 Sjogren´s syndrome vs. non-dry-eye disease and p<0.01 meibomian gland dysfunction vs. non-dry-eye disease); tear break-up time (seconds): Sjogren´s syndrome: 3.97 ± 1.47, meibomian gland dysfunction: 3.95 ± 0.86, non-dry-eye disease: 7.25 ± 1.90 (p<0.01 Sjogren´s syndrome vs. non-dry-eye disease and p<0.01 meibomian gland dysfunction vs. non-dry-eye disease); Lissamine green score: Sjogren´s syndrome-dry-eye: 6.18 ± 2.14, meibomian gland dysfunction-dry-eye: 5.27 ± 1.27, non-dry-eye disease: 1.52 ± 0.97 (p<0.01 Sjogren´s syndrome vs. non-dry-eye disease and p<0.01 meibomian gland dysfunction vs. non-dry-eye disease); impression cytology score: Sjogren´s syndrome: 1.88 ± 0.92, meibomian gland dysfunction: 1.67 ± 0.56, non-dry-eye: 0.45 ± 0.44 (p<0.01 Sjogren´s syndrome vs. non-dry-eye disease and p<0.01 meibomian gland dysfunction vs. non-dry-eye disease) and; tear lysozyme concentration (µg/mL): Sjogren´s syndrome: 751.25 ± 244.73, meibomian gland dysfunction: 1423.67 ± 182.75, non-dry-eye disease: 1409.90 ± 188.21 (p<0.01 Sjogren´s syndrome vs. non-dry-eye disease and p<0.01 Sjogren´s syndrome vs. meibomian gland dysfunction). Conclusion: The concentration of lysozyme in the tears was lower in Sjögren’s syndrome patients than in meibomian gland dysfunction and non-dry-eye disease groups. Hence, the lacrimal lysozyme could be considered as a simple, non-invasive, and economical biomarker to differentiate between Sjögren’s syndrome dry eye disease and meibomian gland dysfunction dry eye disease.